Beethoven recordings reviewed: a systematic method for mapping the content of music performance criticism - Alessandri, Elena; Williamson, Victoria J.; Eiholzer, Hubert; Williamon, Aaron (Frontiers in Psychology, 2015)
Critical reviews offer invaluable, rich data that can be utilized to investigate how musical experiences are conceptualized by experts. However, these data also present significant challenges in terms of organization, analysis, and interpretation. This study presents a new systematic method for examining written responses to music, tested on a substantial corpus of music critique. One hundred critical reviews of Beethoven’s piano sonata recordings, published in the Gramophone between August 1934 and July 2010, were selected using in-depth data reduction (qualitative/quantitative approach). The texts were then examined using thematic analysis in order to generate a visual descriptive model of expert critical review. This model reveals how the concept of evaluation permeates critical review. The model also distinguishes between two types of descriptors. The first characterizes the performance on specific actions or features of the musical sound (musical parameters, technique and energy); the second appeals to higher-order properties (artistic style, character and emotion, musical structure, communicativeness) or assumed performer qualities (understanding, intentionality, spontaneity, sensibility, control, and care). The new model provides a first methodological guide and conceptual basis for future studies of critical review in any genre.